Enhanced algorithm for energy-saving mechanism and frame response time reduction in IEEE 802.16e WiMAX - Baker, Alaa M. (2010)
Mobile Units have many constraints for reliable communication in today’s mobile environments. Unlike wired networks, mobility induces moving around with no power source connected. Hence, an efficient utilization of battery power is important for wireless users. Traffic plays a major role for energy consumption because of the unpredictable incoming flow nature. Many studies have been conducted as an effort to conserve energy and schedule wireless nodes to sleep periodically. The Institute of Electrical and Electronic Engineers (IEEE) standard 802.16, more popularly known as Worldwide Interoperability for Micro Wave Access or WiMAX had finalized the standard IEEE 802.16e for mobile devices. The standard defines a sleep mode operation for conserving power to support the battery life for the mobile broadband wireless access devices. The system saves energy when it goes through a sleeping period. However it faces some delay in the packet arrival response time. The relationship between the energy consumption and the delay is studied to ensure best performance for mobile devices. This relationship has been analyzed by using a mathematical model and a real time scalable model. A new scheduling method is proposed to adjust the sleeping cycle periods by adding a small increase to the next sleeping cycle comparing with the previous cycle. The simulated results had been obtained after adjusting the length of the first sleeping cycle period (Tmin) and adjusting the length of the last sleeping cycle period (Tmax). Adjusting Tmin results in reducing 54% time needed for every frame to get response especially at lower traffic region. At high traffic region, the reduction of 21.5% is obtained in energy consumption for each sleep mode operation. Adjusting Tmax results in reducing 53% of frame response time. Further simulation conducted, showed that the proposed algorithm performs better than the traditional algorithm in reducing the end-to-end delay, and maintains a small reduction in the energy consumption and increases the throughput at the subscriber station. Therefore, the proposed idea confirms a faster frame response time along with lower energy consumption.